PEMBERIAN MIKROALGA YANG BERBEDA TERHADAP PERTUMBUHAN Artemia salina - Erniati Erniati; Erlangga Erlangga; Hairina Hairina (Berkala Perikanan Terubuk, 2012)
Primary factor supporting effective management seed of fish and prawnisqualified natural feed avaibility. Natural feeds used in hatcheryseed for exampleArtemia salina as larva of fish and prawn food’s. One of the factorthat influencingculture growth of Artemia salina is feed. Artemia Salina in nature exploit the feedsuch mikroalga , bacterium, and other organic detritus that hasnutrient content forits growth and sizematching with its mouth. So that mikroalga can be madealternative feed of Artemia salina culture. Various type of mikroalga can be usedas feed like Chaetoceros sp, Skeletonema Costatum and Nannochloropsis oculata.The Mikroalga is very compatible as feed for Artemia salina growth, because hasgood nutrient content. But we have’nt known yet, which most compatible tooptimum growth of artemia.Aim of this research result is to analyzenatural feed of three microalga(Chaetoceros Sp, Skeletonema Costatum and Nannochlropsis oculata) that haveeffect to Artemia Salina growth. Gift of food Chaetoceros sp represent the besttreatment with the long accretion storey;l evel of mean assess 2,99 micron,treatment B of mean 2,76 micron and treatment C represent the treatment 2,57micron. Analyze the data by statistic also indicated that gift different mikroalgaaffect long growth of Artemia Salina.Keywords: Artemia salina, Microalgae